2015
DOI: 10.1161/strokeaha.115.009412
|View full text |Cite
|
Sign up to set email alerts
|

Association of Intraplaque Hemorrhage and Acute Infarction in Patients With Basilar Artery Plaque

Abstract: Background and Purpose-High-resolution magnetic resonance imaging (HRMRI) is ideal for serial examination of diseased arterial walls because it is noninvasive and has superior capability of discriminating tissue characteristics. The aim of this study is to evaluate the prevalence and clinical relevance of intraplaque hemorrhage (IPH) in patients with basilar artery (BA) atherosclerosis using HRMRI. Methods-We analyzed HRMRI and clinical data from 74 patients (45 symptomatic and 29 asymptomatic), all of whom ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
69
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 20 publications
5
69
0
Order By: Relevance
“…Several previous intracranial VWI studies have related HST1 to IPH because of the fact that the major substance of IPH, methemoglobin, has a relatively short T1 relaxation time and, thus, appears hyperintense on T1‐weighted imaging 13, 16. In their work, HST1 was highly associated with ischemic symptoms 13, 16. In another study by Natori et al,18 HST1 was believed to indicate the presence of lipid components in addition to IPH.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Several previous intracranial VWI studies have related HST1 to IPH because of the fact that the major substance of IPH, methemoglobin, has a relatively short T1 relaxation time and, thus, appears hyperintense on T1‐weighted imaging 13, 16. In their work, HST1 was highly associated with ischemic symptoms 13, 16. In another study by Natori et al,18 HST1 was believed to indicate the presence of lipid components in addition to IPH.…”
Section: Discussionmentioning
confidence: 97%
“…Xu et al13 reported HST1 in 19.6% of culprit lesions, and Yu et al16 reported HST1 in 53.3% of culprit lesions. Note that our definition of HST1 is based on whether plaque‐wall CR is >150%, whereas previous studies used different criteria.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, T1, T2 and PD weighted IVWM hyperintensity was found to be more common among symptomatic (57.1 %) vs. asymptomatic (22 %) MCA plaques [42], a finding which has been replicated in several studies [43,44]. In the posterior circulation, a study of 73 patients with >50 % BA stenosis found that IPH, detected on the nonblood suppressed 3D magnetization-prepared rapid gradient-echo (MP-RAGE) sequence, was associated with a 1.64 relative risk of a focal stroke event on DWI (p < 0.01), with a sensitivity of 80.0 % and specificity of 46.5 % [45].…”
Section: Introductionmentioning
confidence: 73%